IMPLEMENTASI PENGAMBILAN KEPUTUSAN PEMBELIAN KEBUTUHAN DALAM MENGELOLA UANG SAKU SANTRIWAN PONDOK PESANTREN MATHLA’UL ANWAR - Mohamad Khairil Anam; Nuraini Asriati; Maria Ulfah (Universitas Tanjungpura, 2019)
Abstract This study aimed to determine how the purchasing decision-making process needs in managing students pocket money of Islamic Boarding School Of Mathla’ul Anwar Pontianak. The method of this research was applied by qualitative research approach. The subject of this research was the students of Islamic Boarding School Of Mathla’ul Anwar which consisted of 12 students. The technique of collecting the data of this resarch was applied by observation, direct communication, field notes, and documentary techniques. While the data collection tools used interviews, observation sheets, and field notes. For the data management technique it was applied by qualitative analysis technique. The results of this study was obtained from interviews and observations. For the indicators purchasing decision making it can be concluded that the Students of Islamic Boarding School of Mathla'ul Anwar Pontianak can in reach their needs through several steps, which are : (1) Needs Introduction, (2) Information Search, (3) Evaluation Alternatives, (4) Purchasing Decisions, (5) Post-Consumption Behavior.Keywords: Decision Making, Money Pocket, Needs Purchasing